A synchronous improvement of strength and elongation caused by solid solution in low-silver SAC solder with superior necking resistance properties - Xiaojing Wang; Shuhua Zhang; Jiaheng Zhang; Shanshan Cai; Ning Liu; Yan Lai Wang (Journal of Materials Research and Technology)
The current SAC(Sn–Ag–Cu) solder often experiences rapid degradation of mechanical properties at high temperatures and is prone to fracture under dynamic loads, thus failing to meet the interconnection requirements of industrial electronic products that operate under high power and vibration loads. In light of this, this paper aims to enhance the overall performance of the alloy by reducing the fraction of the second phase in SAC305 alloy, altering the type of second-phase particles, and strengthening the matrix β-Sn phase. Additionally, based on thermodynamic calculations of phase diagrams, the internal phases and elemental solid solubility of the alloy under different temperature conditions are accurately designed, thereby improving the alloy's strength while maintaining its elongation almost unchanged. The experimental results indicate that the designed Sn1.0Ag0.7Cu–3Bi4In1.5Sb alloy exhibits a higher rate sensitivity factor m (0.0559), which is more than double that of the Sn1.0Ag0.7Cu–5Bi4In3Sb alloy (0.0239). This improvement is primarily attributed to the enhanced interaction between the matrix β-Sn and the solid solution effect. Larger compound phases, such as Cu6Sn5 and Ag3Sn, only play a role in the low-rate loading region. Additionally, the alloy demonstrates strong temperature dependence, which is also related to the dissolution of the In element in the matrix β-Sn. The solid solution of the In element significantly enhances the high-temperature elongation rate of the alloy, increasing from 11.9% at low temperatures to 21.3% at high temperatures. The successful development and implementation of this research provides a new solution for interconnection of electronic devices under high-speed dynamic loading and high-temperature service.